The Performance and Interrater Agreement of Vibration Perception for the Diagnosis of Loss of Protective Sensation in People With Diabetes Mellitus. (March 2023) - Tentolouris, Anastasios; Tentolouris, Nikolaos; Eleftheriadou, Ioanna; Jude, Edward B.
This study examined the performance of VibraTip for the diagnosis of loss of protective sensation (LOPS) and the interrater agreement of different neurological modalities performed by 3 health care professionals, a consultant diabetologist, a diabetes specialist nurse, and a podiatrist. Diagnosis of LOPS was based on 10-g Semmes Weinstein monofilament testing performed by a consultant diabetologist (reference method), while examination with a 128-Hz tuning form was also performed. The performance of VibraTip for the diagnosis of LOPS was examined using the receiver operating characteristic curves analysis. Interrater agreement was determined by weighted kappa (κ) statistics. Diagnosis of LOPS (%) was 37.5%. Receiver operating characteristic curve analysis showed that VibraTip examination versus 10-g monofilament, both performed by a consultant, could diagnose LOPS ( P < .001). Sensitivity, specificity, positive predictive value, and negative predictive value of VibraTip versus 10-g monofilament, both performed by a consultant (value, 95% confidence interval), was 0.705 (0.591-0.803), 0.836 (0.758-0.897), 0.733 (0.642-0.808), and 0.816 (0.757-0.863), respectively. The interrater agreement among the health care professionals for 10-g monofilament, VibraTip, and 128-Hz tuning fork in neurological assessment was good with κ > 0.61. VibraTip can be used as a screening tool for the detection of LOPS. There was good overall agreement in the results of neurological examination using 10-g monofilament, 128-Hz tuning fork, and VibraTip among health care professionals.